Improving pedestrian’s facilities management for the safety of road users in Universiti Utara Malaysia, Sintok, Kedah - Loh, Tong Cheng; Anuar, Nur Khairiel (2012)
The road users or pedestrians are one of the transport modes where relatively unprotected road users interact with traffic of high speed and mass.This makes pedestrians vulnerable.They suffer the most severe consequences in collision with other road users because they cannot protect themselves against the speed and mass of the other party. At the Universiti Utara Malaysia (UUM), the facilities infrastructure is also can endanger the students.Some of the facilities infrastructure is not well maintained by the university.The students may not realize the danger situation until it happen.The vulnerability, instability, differing abilities and estrangement of the infrastructure facilities will be determine through the research.The research intends use qualitative method and questionnaire to address the problem.After that, the research compares the result with the other journals example.The purpose of the research is to address the problem whether the infrastructure facilities can enhance the safety of the pedestrians.